Multiple Endocrine Neoplasia Type 1 with Concomitant Existence of Malignant Insulinoma: A Rare Finding - Randhir Sagar Yadav; Ashik Pokharel; Deepshikha Gaire; Shumneva Shrestha; Ashbita Pokharel; Sumita Pradhan; Prasan Bir Singh Kansakar (Case Reports in Endocrinology)
Multiple endocrine neoplasia type 1 (MEN1) is a rare syndrome of autosomal dominant inheritance defined by co-occurrence of two or more tumors originating from the parathyroid gland, pancreatic islet cells, and/or anterior pituitary. Insulinoma which has an incidence of 0.4% is a rare pancreatic neuroendocrine tumor. Malignant insulinoma is extremely rare, while primary hyperparathyroidism is a common occurrence in MEN1. We present a case of MEN1 syndrome with 2.6 cm insulinoma in the pancreatic head and parathyroid adenoma in a 56-year-old female who presented with symptoms suggestive of hypoglycemia like multiple episodes of loss of consciousness for four years. Classical pancreaticoduodenectomy was carried out, and the postoperative period was uneventful. Later, subtotal parathyroidectomy was performed, which showed parathyroid adenoma. Patients presenting with features of hypoglycemia should be vigilantly assessed for the presence of a sinister pathology.